PENGHILANGAN GAS SO2 (SULFUR DIOKSIDA) DENGAN TEKNIK BIOFILTER MENGGUNAKAN Thiobacillus sp. PADA MEDIA SERBUK GERGAJI, KOMPOS DAN TANAH - Nastitit Siswi Indrasti, Mohamad Yani dan Sugyanto P. Manik (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTSulphur dioxide is one of the hazardous substances. Most of SO2 is emitted from oil burning. SO2 was effectively removed by biofilter technique using Thiobacillus sp. in compost, saw dust, and top soil media. On the biofilter without Thiobacillus sp.with the inlet concentration of SO2 2396,10 µg/m3; the saturated time is shorter than that on the biofilter with Thiobacillus sp. addition. Saturated time without Thiobacillus sp. in the compost biofilter was a 12 hour, in top soil biofilter was 18 hours, and in the saw dust biofilter was 0,5 hoursThe removal capacity of SO2 with Thiobacillus sp. in the compost biofilter was 4,12 mg-S/ /kg compost-dayl, while in the biofilter top soil was 3,12 mg-S/kg top soil-day. Thiobacillus sp. addition in the saw dust biofilter did not affect the ability of SO2 degradation. There were 3 levels of SO2 inlet concentration, ie: 2396,10 µg/m3, 4632,29 µg/m3, and 9331,68 µg/m3. Compost biofilter effectively worked in 19 days while top soil biofilter worked in 22 days. Saw dust was saturated at the first day of the process. Keywords : Biofilter, Thiobacillus sp., SO2 degradation, compost, top soil, saw dust